Industrial and Technological Applications of Power Electronics Systems - Strzelecki, Ryszard; Demidova, Galina; Vinnikov, Dmitri (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Special Issue "Industrial and Technological Applications of Power Electronics Systems" focuses on: - new strategies of control for electric machines, including sensorless control and fault diagnosis; - existing and emerging industrial applications of GaN and SiC-based converters; - modern methods for electromagnetic compatibility. The book covers topics such as control systems, fault diagnosis, converters, inverters, and electromagnetic interference in power electronics systems. The Special Issue includes 19 scientific papers by industry experts and worldwide professors in the area of electrical engineering.